Development of Islamic Values for Deaf Students at Little Hijabi Homeschooling - Rosalia Canida; Dian Dian; Iin Hindasah Noor (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The aims of this study were is to analyze the development of Islamic values for deaf students at The Little Hijabi Homeschooling; learn Islamic values applied to deaf students, especially in early childhood; examine the supporting and inhibiting factors in implementing the Islamic values and the way of The Little Hijabi Homeschooling in educating and developing Islamic values curriculum. The research method used was descriptive qualitative method and literature study. Data collection techniques in this study include is observation; interview; and documentation; searching for data through websites or journals. Qualitative data analysis used in this study with data reduction, data presentation, and drawing conclusions. It can be said that the development of Islamic values for deaf students, especially students at an early age, is very good and different from special schools used by people with disabilities in general which are only limited to PAI learning without any in-depth learning in applying the form of monotheism and Iqro learning with sign language